Biological magnesium-based composite material with gradient structure and preparation method thereof
A bio-magnesium-based composite material with a gradient structure addresses rapid degradation and mechanical failure by enhancing mechanical and corrosion resistance through controlled grain size and distribution, ensuring structural integrity and biocompatibility.
Patent Information
- Application Number
- CN202411256480.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
Existing technologies fail to address the challenges of mechanical and corrosion resistance of magnesium-based materials, and the degradation of magnesium-based materials, and the degradation of hydrogen production, leading to rapid degradation and mechanical failure of magnesium-based implants.
A bio-magnesium-based composite material with a gradient structure, composed of 5.0% Mn, 3.5-6.5% Zn, and inevitable impurities, featuring dual-scale Mn particle reinforcements and controlled grain size distribution, prepared through multi-directional rolling friction to enhance mechanical and corrosion resistance.
The composite material exhibits improved mechanical properties and corrosion resistance, maintaining structural integrity and biocompatibility, reducing the risk of premature failure and secondary infections.
Smart Images

Figure CN119121014A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of light metal-based composite material preparation, and in particular to a bio-magnesium-based composite material with a gradient structure and a preparation method thereof. Background Art
[0002] Traditional medical metal implant materials, such as stainless steel, titanium alloy, cobalt alloy, etc., have high strength, excellent ductility and good corrosion resistance, and have been widely used in the biomedical field. However, traditional medical metal implant devices cannot degrade spontaneously. After the human tissue repairs itself, a second operation is required to remove them, which increases the risk of secondary infection and the economic burden on patients. Magnesium metal and its alloys have shown broad application prospects in the fields of coronary artery intervention, biliary intervention, dental implants, bone repair and fixation due to their biodegradability, density and elastic modulus close to human bones, and good biocompatibility. However, the application of magnesium alloys in the field of biomaterials is still in the research and development stage. The core challenge is that they degrade too fast under physiological conditions and produce too much hydrogen. This characteristic directly leads to a significant decrease in tissue cell activity and mechanical support capacity. Due to the rapid degradation process, it is difficult for the material to maintain its structural integrity for a long time in the body, which eventually leads to the functional failure of the implant, limiting its application and promotion in clinical treatment.
[0003] Conventional alloying combined with plastic deformation can strengthen magnesium alloys, but this will reduce corrosion resistance. However, the key to whether it can replace traditional medical materials is how to improve strength while maintaining or improving corrosion resistance through the comprehensive use of mechanisms such as fine grain strengthening, second phase strengthening, solid solution strengthening and dislocation strengthening. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the present invention provides a method for improving the mechanical and corrosion resistance of magnesium-based materials by multi-directional rolling friction. The technical problem to be solved by the present invention is to select a Mg-Zn-Mn system under the condition of meeting biological safety, and for small-sized samples, efficiently refine the surface grains while ensuring that the sample does not bend and deform during rolling friction, and regulate the size and distribution of Mn particles, so as to solve the problems of fast corrosion rate, large hydrogen production, and easy failure of small-sized magnesium-based materials during initial implantation.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0006] A bio-magnesium-based composite material with a gradient structure, wherein the magnesium-based composite material is composed of the following components calculated by mass percentage:
[0007] 5.0% Mn, 3.5-6.5% Zn, inevitable impurity elements, the balance is Mg;
[0008] The magnesium-based composite material has metal Mn particle reinforcements of dual scales of micrometer and nanometer, wherein the size of the Mn particle reinforcements in the magnesium-based composite material is 5-200nm and 1-20μm, and the grain size of the magnesium-based composite material is 50nm-30μm.
[0009] Preferably, when the magnesium-based composite material is a rod, the size of the Mn particles near its outer surface is 5nm to 200nm; the size of the Mn particle reinforcement near the core of the rod is nanometer-level and micrometer-level, the nanometer size is 5 to 200nm, and the micrometer size is 1 to 20μm. Wherein, the core is the axis of the rod along its length direction.
[0010] Preferably, the grain size of the magnesium-based composite material gradually increases from its outer surface to its core.
[0011] Preferably, the grain size of the magnesium-based composite material gradually increases from 50 nm on the outer surface to 30 μm toward the core.
[0012] The present invention provides a method for preparing a magnesium-based composite material. The specific steps for preparing the magnesium-based composite material are as follows:
[0013] Step 1: prepare pure magnesium, pure zinc and magnesium-manganese master alloy as raw materials according to the component ratio;
[0014] Step 2: Melting the raw materials prepared in step 1 to obtain a composite melt, rapidly cooling the composite melt to obtain an ingot, and performing a solid solution treatment on the ingot;
[0015] Step 3: hot extruding the ingot processed in step 2 to obtain a rod; wherein the specific steps of hot extrusion are as follows:
[0016] The ingot is preheated at 300-400°C for 1-2h, and hot extruded at 300-400°C to obtain a rod, with an extrusion ratio of (10:1)-(100:1) and an extrusion speed of 0.1-1.0 m / min;
[0017] Step 4: Perform three-way rolling friction treatment on the rod obtained in step 3 to obtain a bio-magnesium-based composite material with a gradient structure; wherein the rod diameter is ≥1mm, the rotation speed of the rod is 10-100r / min, the rolling friction pressure of the rod is 10-200N, and the radial deformation is 2-6%.
[0018] Preferably, in step 2, smelting is carried out in a protective atmosphere environment, first the magnesium ingot is smelted at 720-740°C, and after it is completely melted, the temperature is adjusted to 740°C, a magnesium-manganese intermediate alloy is added, and finally pure zinc is added, and after all the raw materials are melted, they are fully stirred, the surface scum is knocked off, and they are rapidly cooled to obtain a melt.
[0019] Preferably, in step 2, the process conditions of the solution treatment are: keeping warm at 380-420° C. for 6-12 hours.
[0020] Preferably, in step 3, in the magnesium-based composite material after the treatment in step 3, micrometer- and nanometer-scale metal Mn particles are dispersed in the rod, and the sizes thereof are 1 to 20 μm and 5 to 200 nm; and the size range of the grains in the magnesium-based composite material is 1 to 30 μm.
[0021] Preferably, in the magnesium-based composite material after treatment in step 4, the size of the Mn particle reinforcement on its surface is 5 to 200 nm; the size of the Mn particle reinforcement inside it is 1 to 20 μm and 5 to 200 nm, and the grain size of the magnesium-based composite material gradually increases from the surface to the inside, and is 50 nm to 30 μm.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The present invention limits the weight percentage of Mn in the composite material to 5.0%. First, Mn is one of the essential trace elements for the human body and has good biocompatibility. Mn is mainly present in the Mg-Zn-Mn system as a single α-Mn phase; and Mn is evenly distributed in the Mg-Zn matrix alloy in the form of micron-scale and nanometer dual-scale particles to play a strengthening role; and these dispersed micro-nano composite α-Mn particles can promote dynamic recrystallization nucleation during dynamic recrystallization, and hinder the growth of dynamic recrystallization grains, which is beneficial to grain refinement, thereby ensuring that the material can obtain a fine recrystallized structure. In addition, the addition of Mn can also reduce impurity elements such as Fe, Ni, Cu, and Si in the melt to a certain extent, improve corrosion resistance and biocompatibility, and further limit the negative impact of impurity elements on the degradation behavior of material implantation.
[0024] 2. The present invention limits the weight percentage of Zn to 3.5% to 6.5%. First, Zn is one of the essential trace elements for the human body and has good biocompatibility. If the Zn content is too low, it will not effectively reduce the energy barrier of nanocrystal nucleation, and thus cannot provide favorable conditions for the nucleation of nanocrystals. At the same time, it is not conducive to the formation of a dense zinc-containing protective film during the subsequent implantation process, and thus cannot effectively hinder the corrosion of the corrosive medium on the magnesium matrix, resulting in a decrease in the corrosion resistance (especially the initial corrosion resistance) of the magnesium-based composite material, and at the same time, it cannot produce sufficient grain boundary pinning effect, resulting in the inability to effectively inhibit the growth of nanocrystals after rolling friction; if the Zn content is too high, a large amount of banded tissue will be formed, and it is very easy to thermally crack during the extrusion deformation process.
[0025] 3. The magnesium-based composite material with a gradient structure prepared by the present invention can be rubbed three times while the rod rotates one circle through an improved three-dimensional rolling friction mold during the preparation process, which greatly improves the rolling friction efficiency. The dislocation and twins generated by the previous rolling friction can be used as pretreatment for the next rolling friction, and rolling friction can be achieved under low deformation and low rotation speed conditions. In addition, the rod is subjected to three-dimensional pressure during the three-dimensional rolling friction process, which avoids the rolling friction bending deformation of small-sized samples, and the rod is more prone to twin deformation. The generation of a large number of twins can better promote grain refinement and form nano-grains. The three-dimensional pressure can achieve more precise size control of small-sized samples, and it is also more helpful to eliminate defects and cracks inside the material. The present invention optimizes the preparation process and achieves the purpose of preparing small-sized biological magnesium-based composite materials at low rotation speed and high efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is the high-angle annular dark field image and energy spectrum results of the surface microstructure.
[0027] Figure 2 Metallographic photograph of multi-directional rolling friction sample.
[0028] Figure 3 The macroscopic morphology of the examples and comparative examples after immersion and stretching fracture.
[0029] Figure 4 The morphology and distribution diagram of Mn particles in the examples and comparative examples are shown.
[0030] Figure 5 Comparison chart of one-way rolling friction and three-way rolling friction macro samples.
[0031] Figure 6 Schematic diagram of the three-way rolling friction treatment of the present invention. DETAILED DESCRIPTION
[0032] The present invention will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the present invention belong to the scope of protection of the present invention.
[0033] Unless otherwise indicated in specific cases in the present invention, the numerical ranges listed herein include the upper and lower limits, and all integers and fractions within the range, and are not limited to the specific values listed when defining the range.
[0034] 1. A bio-magnesium-based composite material with gradient structure
[0035] Calculated by mass percentage, the magnesium-based composite material of the present invention consists of the following components:
[0036] 5.0% Mn, 3.5-6.5% Zn, inevitable impurity elements, the balance is Mg;
[0037] The magnesium-based composite material has metal Mn particle reinforcements of dual scales of micrometer and nanometer, wherein the size of the Mn particle reinforcements in the magnesium-based composite material is 5-200nm and 1-20μm, and the grain size of the magnesium-based composite material is 50nm-30μm.
[0038] After studying the existing medical metal implant magnesium alloy materials, the present invention found that the ideal implant material should exhibit a precisely controlled degradation characteristic: the initial degradation rate is slow to avoid premature failure of the implant; and the degradation is accelerated in the later stage, so as not to prolong the patient's recovery period. However, the prior art often introduces alloying elements to regulate the recrystallization process of magnesium alloys, refine the grains, and thus significantly enhance their mechanical properties, which has become an important strategy. However, this method inevitably introduces a second phase, and the potential difference between these second phases and the magnesium matrix may aggravate the sensitivity of local corrosion, making the corrosion rate of magnesium alloys during implantation difficult to predict and control, especially when the magnesium alloy matrix itself is prone to local corrosion. If the distribution of alloying elements is uneven, corrosion micro-batteries will also be formed in the magnesium alloy, further accelerating corrosion and causing serious uneven degradation. In response to this problem, the prior art also considers surface modification of the alloy surface to improve the corrosion resistance of the magnesium alloy in the early stage of implantation, but the thickness and uniformity of the coating are often difficult to control, and it is easy to fall off or peel off under stress. This will not only affect the protective effect of the coating, but also threaten the safety and stability of the implant. Not only the above-mentioned problems exist in the selection and adjustment of raw materials, the present invention further finds that in the prior art technology for preparing such materials, there are patent applications for improving the mechanical properties and corrosion resistance of magnesium alloys through steps such as surface rolling strengthening treatment. However, the entire process does not consider small-sized samples of biomaterials, as well as magnesium-based composite materials. In this type of technology, rod-shaped samples are subjected to unidirectional or bidirectional forces during the rolling friction process, which results in rolling friction that easily causes bending deformation of the rods when preparing small-sized samples, and it is impossible to prepare small-sized products with excellent mechanical properties and corrosion resistance. Therefore, the present invention makes adjustments in three aspects: the type of elements in the raw materials, the amount used, and the preparation method. The present invention improves the preparation method so that the obtained biological magnesium-based composite material has a gradient structure, wherein the grain size in the magnesium-based composite material presents a gradient distribution from the surface to the inside, the surface reinforcement size is 5-200nm, and there are micron and nano composite reinforcements in the core, and the sizes are 5-200nm and 1-20μm, respectively. It is necessary to maintain its ideal degradation characteristics as an implant material, and effectively avoid the risks brought by local corrosion and uneven degradation, so as to ensure the effectiveness and biosafety of the implant.
[0039] In some embodiments, the amount of Mn element is controlled at 5%, and Mn is mainly dispersed in the Mg-Zn matrix alloy in the form of micron and nanometer dual-scale α-Mn particles to play a reinforcing role; and these dispersed α-Mn particles can promote dynamic recrystallization as nucleation sites during dynamic recrystallization, and hinder the growth of recrystallized grains, which is beneficial to the refinement of recrystallized grains, thereby ensuring that the material can better play a fine grain strengthening role. If the amount of Mn element is too low, a sufficient number of micron and nano α-Mn particles cannot be formed, and it is difficult to play a role in strengthening and refining grains for magnesium alloy materials; and if the amount of Mn element is too high, a large number of non-recrystallized areas will appear in the material, which may reduce the uniformity of the material's organization, increase the average grain size, and affect the performance of the composite material.
[0040] In some embodiments, the amount of Zn element is controlled between 3.5% and 6.5%. If the Zn content is too low, it cannot effectively reduce the energy barrier for the nucleation of nanocrystals, and thus cannot provide favorable conditions for the nucleation of nanocrystals. At the same time, it cannot participate in the formation of a dense protective film in the subsequent implantation process, and thus cannot effectively hinder the corrosion of the corrosive medium on the magnesium matrix, resulting in a decrease in the corrosion resistance (especially the initial corrosion resistance) of the magnesium-based composite material. At the same time, it cannot produce sufficient grain boundary pinning effect, resulting in the inability to effectively inhibit the growth of nanocrystals after rolling friction, and the mechanical properties are not significantly improved; if the Zn content is too high, a large amount of banded tissue will be formed, and it is very easy to thermally crack during the extrusion deformation process.
[0041] In some embodiments, in the magnesium-based composite material, the size of the Mn particle reinforcement is 5nm to 20μm, and the number of micron-sized Mn particles gradually increases from the surface of the magnesium-based composite material to the inside thereof, and the number of nano-sized Mn particles gradually decreases. The increase of nano-sized Mn particles can increase the open circuit potential and reduce the tendency to corrosion. The grain size in the magnesium-based composite material of the present invention has a gradient structure, and the grain size in the magnesium-based composite material gradually increases from the surface to the inside thereof, so that the magnesium-based composite material presents a multi-level gradient structure. It further blocks the direct contact between corrosive media such as chloride ions and the matrix alloy, and the Mn oxide protective film formed by the participation of nano-sized Mn particles has higher chemical stability and density, reducing the corrosion rate of the material.
[0042] 2. A method for preparing a magnesium-based composite material
[0043] Step 1: prepare pure magnesium, pure zinc and magnesium-manganese master alloy as raw materials according to the component ratio;
[0044] Step 2: Melting the raw materials prepared in step 1 to obtain a composite melt, rapidly cooling the composite melt to obtain an ingot, and performing a solid solution treatment on the ingot;
[0045] Step 3: hot extruding the ingot processed in step 2 to obtain a rod; wherein the specific steps of hot extrusion are as follows:
[0046] The ingot is preheated at 300-400°C for 1-2h, and hot extruded at 300-400°C to obtain a rod, with an extrusion ratio of (10:1)-(100:1) and an extrusion speed of 0.1-1.0 m / min;
[0047] Step 4: Perform three-way rolling friction treatment on the rod obtained in step 3 to obtain a bio-magnesium-based composite material with a gradient structure; wherein the rod diameter is ≥1mm, the rotation speed of the rod is 10-100r / min, the rolling friction pressure of the rod is 10-200N, and the radial deformation is 2-6%.
[0048] In the present invention, the rod is subjected to a three-way rolling friction treatment, which means that the rod is subjected to rolling friction treatment from three different contact points along the circumference of the rod, so that the rod can be subjected to forces from three different directions, and the positions of the three different contact points can be further optimized to be evenly spaced along the circumference of the rod. The diameter of the rod can be 1-16 mm.
[0049] In some embodiments, in step 2, smelting is carried out in a protective atmosphere environment, first the magnesium ingot is smelted at 720-740°C, and after it is completely melted, the temperature is adjusted to 740°C, a magnesium-manganese intermediate alloy is added, and finally pure zinc is added, and after all the raw materials are melted, they are fully stirred and the surface scum is removed to obtain a melt.
[0050] In some embodiments, in step 2, the process conditions of the solution treatment are: keeping warm at 380-420° C. for 6-12 hours.
[0051] In some embodiments, in step 3, the specific steps of hot extrusion are as follows:
[0052] The ingot is preheated at 300-400°C for 1-2h, and hot extruded at 300-400°C to obtain a rod, with an extrusion ratio of (10:1)-(100:1) and an extrusion speed of 0.1-1.0m / min.
[0053] In some embodiments, in the magnesium-based composite material after the treatment in step 3, Mn particle reinforcements are uniformly distributed inside the magnesium-based composite material, and the sizes thereof are 1 to 20 μm and 5 to 200 nm; and the average size of the grains in the magnesium-based composite material is 1 to 30 μm.
[0054] In some embodiments, in step 4, the diameter of the rod is ≥1 mm, the rotation speed is 10-100 r / min, the rolling friction pressure of the rod is 10-200 N, and the radial deformation is 2-6%.
[0055] In some embodiments, in the magnesium-based composite material after step 4, the size of the Mn particle reinforcement in its interior is 1 to 20 μm and 5 to 200 nm, and the size of the Mn particle reinforcement on its surface is 5 to 200 nm; the average size of the grains of the magnesium-based composite material increases from 50 nm on the surface to 30 μm in the core.
[0056] 3. Examples and Comparative Examples
[0057] 1. Adjustment of raw material ratio
[0058] Example 1
[0059] Step 1: prepare pure magnesium, pure zinc and magnesium-manganese master alloy as raw materials according to the composition ratio in Table 1;
[0060] Step 2: Melt in a protective atmosphere, first melt the magnesium ingot at 720-740℃, adjust the temperature to 740℃ after it is completely melted, add magnesium-manganese master alloy, and finally add pure zinc. After all the raw materials are melted, stir them fully, remove the surface scum, and quickly cool them with water to obtain a melt. The process conditions for solution treatment are: keep warm at 380℃ for 8h.
[0061] Step 3: hot extruding the ingot processed in step 2 to obtain a rod; the specific steps of hot extrusion are as follows:
[0062] The ingot was preheated at 350°C for 1 h and hot extruded at 350°C to obtain a rod with an extrusion ratio of 25:1 and an extrusion speed of 1.0 m / min.
[0063] Step 4: Perform three-way rolling friction treatment on the rod obtained in step 3 to obtain a bio-magnesium-based composite material with a gradient structure. In step 4, the rotation speed of the rod is 100 r / min, the multi-way rolling friction pressure of the rod is 200 N, and the radial deformation of the rod is 3.5%.
[0064] Example 2
[0065] Adjustments were made based on Example 1, except that the raw material components were different, see Table 1 for details; the other preparation steps were the same as Example 1.
[0066] Comparative Example 1
[0067] Adjustments were made based on Example 1, except that the raw material components were different, see Table 1 for details; the other preparation steps were the same as Example 1.
[0068] Comparative Example 2
[0069] Adjustments were made based on Example 1, except that the raw material components were different, see Table 1 for details; the other preparation steps were the same as Example 1.
[0070] Comparative Example 3
[0071] Adjustments were made based on Example 1, except that the raw material components were different, see Table 1 for details; the other preparation steps were the same as Example 1.
[0072] According to the components in Table 1, comparative examples 1 to 3 were prepared by the methods of examples 1 to 2 to verify the influence of the raw material composition ratio on the performance of the magnesium-based composite material.
[0073] Table 1 Group distribution ratio (unit: wt%)
[0074]
[0075] The tensile mechanical properties of the magnesium-based composite materials prepared in Examples 1 to 2 and Comparative Examples 1 to 3 were tested, wherein the extruded state refers to the rod obtained after the treatment in step 3, and the results of the mechanical properties test are performed on it; the multi-directional rolling friction state refers to the rod obtained after the treatment in step 4, and the results of the mechanical properties test are performed on it. The results are shown in Table 2.
[0076] Table 2
[0077]
[0078] From the above two tables, we can see that:
[0079] (1) The embodiment is based on the Mg-Zn-Mn composite material rod, and its tensile mechanical properties are more significantly improved after rolling friction. Specifically, the co-addition of Zn element and Mn particles causes the material to undergo dynamic recrystallization during the hot extrusion process. Mn particles and the second phase formed by Zn element can play a role in pinning grain boundaries and inhibiting grain growth, further obtaining a finer and more uniform dynamic recrystallization structure. Rolling friction introduces gradient nanostructures and dual-scale Mn particles, and the size difference between the surface fine grains and the core coarse grains is more conducive to the heterogeneous deformation induced strengthening and HDI strengthening of the grains, and shows better synergy with traditional strengthening (fine grain strengthening, second phase strengthening, solid solution strengthening and dislocation strengthening).
[0080] (2) Regardless of the embodiment or the comparative example, the mechanical properties of the rod are indeed improved after the multi-directional rolling friction treatment, which indicates that the treatment method of the present invention can bring about a significant improvement in the mechanical properties of the magnesium-based composite material.
[0081] (3) Due to the lack of Zn element in Comparative Example 1, the solid solution strengthening and second phase strengthening effects of the material are weakened. The mechanical properties of Comparative Example 1 obtained after hot extrusion treatment are not as good as those of Example 1; even after multi-directional rolling friction treatment, the improvement in mechanical properties is still not as good as that of Example 1; this situation also occurs in Comparative Examples 2 to 3, which shows that the insufficient amount of Mn and Zn elements cannot achieve the improvement of the mechanical properties of the magnesium-based composite material.
[0082] 2. Adjustment of the radial deformation of the bar
[0083] The present invention adopts the Mg-Zn-Mn system as the research object. The material components are all non-toxic or beneficial elements to the human body, have good biocompatibility, and the mechanical properties are also improved. However, the problem of accelerated degradation caused by the galvanic corrosion of the second phase and the reinforcement, as well as the problem of local corrosion, easily cause implant failure. The present invention prepares magnesium-based rods by two-step continuous plastic processing, the surface structure is significantly refined, and the size and distribution of the reinforcement are regulated, the corrosion resistance of the material is improved, and the corrosion failure mode in the early stage of implantation is transformed from local corrosion to uniform corrosion, thereby solving the problem of premature failure of mechanical properties due to too fast degradation of magnesium implant devices in the early stage. The ratio of the tensile strength of the material after 7 days of simulated body fluid immersion to that before immersion is ≥95%.
[0084] Example 3
[0085] Step 1: preparing pure magnesium, pure zinc and magnesium-manganese master alloy as raw materials according to the component proportions of Example 1 in Table 1;
[0086] Step 2: Melt in a protective atmosphere, first melt the magnesium ingot at 720-740℃, adjust the temperature to 740℃ after it is completely melted, add magnesium-manganese master alloy, and finally add pure zinc. After all the raw materials are melted, stir them fully, remove the surface scum, and quickly cool them with water to obtain a melt. The process conditions for solution treatment are: keep warm at 380℃ for 8h.
[0087] Step 3: hot extruding the ingot processed in step 2 to obtain a rod; the specific steps of hot extrusion are as follows:
[0088] The ingot was preheated at 330°C for 1 h and hot extruded at 330°C to obtain a rod with an extrusion ratio of 50:1 and an extrusion speed of 1.0 m / min.
[0089] Step 4: The rod obtained in step 3 is subjected to three-way rolling friction treatment to obtain a bio-magnesium-based composite material with a gradient structure. In step 4, the rotation speed of the rod is 100 r / min, the multi-way rolling friction pressure of the rod is 200 N, and the radial deformation of the rod is 2%.
[0090] Example 4
[0091] An improvement is made on the basis of Example 3, and the difference therefrom is that the radial deformation amount is different, which is 3.5%; the other steps are the same as Example 3.
[0092] Comparative Example 4
[0093] An improvement is made on the basis of Example 3, and the difference therefrom is that the radial deformation amount is different, which is 7.5%; the other steps are the same as Example 3.
[0094] Comparative Example 5
[0095] An improvement is made on the basis of Example 3, and the difference therefrom is that the radial deformation amount is different, which is 0%; the other steps are the same as Example 3.
[0096] Examples 3 to 4 and Comparative Examples 4 to 5 all use the component proportions of Example 1 in Table 1 for compounding, but use different extrusion deformation processes and rolling friction radial deformation amounts.
[0097] Table 3
[0098]
[0099] The mechanical properties of the magnesium-based composite materials prepared in Examples 3 to 4 and Comparative Examples 4 to 5 were tested, and the room temperature tensile specimens were immersed in m-SBF simulated body fluid for 7 days, and then cleaned and dried to perform room temperature tensile tests. The room temperature mechanical properties of the three specimens were measured, and the average tensile strength of the material was taken as the tensile strength of the composite material after immersion in simulated body fluid. The ratio of the tensile strength of the material to the tensile strength of the material before immersion in simulated body fluid was taken as the ratio of the tensile strength of the material after 7 days of immersion in simulated body fluid to that before immersion, as a criterion for judging the material's ability to resist corrosion from simulated body fluids. The closer the value is to 1, the higher the material's ability to resist corrosion from simulated body fluids. The results are shown in Table 4, m-SBF simulated body fluid (ion concentration is shown in Table 5).
[0100] Table 4
[0101]
[0102] Table 5
[0103]
[0104] From Tables 3 and 4, we can see that:
[0105] From the comparison of the data of Examples 3-4 and Comparative Examples 4-5 in Table 4, it can be seen that multi-directional rolling friction can significantly reduce the initial degradation rate of the magnesium-based composite material and increase the ratio of the tensile strength of the composite material after 7 days of simulated body fluid immersion to that before immersion. The change in the radial deformation of the rod significantly affects the corrosion resistance rate of the rod. The appropriate multi-directional rolling friction process can achieve strength-plasticity synergy. At the same time, after 7 days of immersion, the pH value of the embodiment changes little, which also shows that the magnesium-based composite material prepared in the embodiment has a low initial degradation rate.
[0106] 3. Comparison of unidirectional and multidirectional rolling friction processes
[0107] The preparation of small-sized biological magnesium-based samples usually requires precision processing technology. Rolling friction under unidirectional force is unlikely to ensure that the sample has an accurate size and shape. Therefore, the present invention specifically invents a small-sized rolling friction process and compares it with the unidirectional rolling friction process.
[0108] Example 5
[0109] Step 1: prepare pure magnesium, pure zinc and magnesium-manganese master alloy as raw materials according to the composition ratio in Table 1;
[0110] Step 2: Melt in a protective atmosphere, first melt the magnesium ingot at 720-740℃, adjust the temperature to 740℃ after it is completely melted, add magnesium-manganese master alloy, and finally add pure zinc. After all the raw materials are melted, stir them fully, remove the surface scum, and quickly cool them with water to obtain a melt. The process conditions for solution treatment are: keep warm at 380℃ for 8h.
[0111] Step 3: hot extruding the ingot processed in step 2 to obtain a rod; the specific steps of hot extrusion are as follows:
[0112] The ingot was preheated at 350°C for 1 h and hot extruded at 350°C to obtain a rod with an extrusion ratio of 50:1 and an extrusion speed of 1.0 m / min.
[0113] Step 4: The rod obtained in step 3 is machined into a 2.5 mm rod to obtain a bio-magnesium-based composite material with a gradient structure. In step 4, the rotation speed of the rod is 100 r / min, the multi-directional rolling friction pressure of the rod is 200 N, and the radial deformation of the rod is 3.5%.
[0114] Example 6
[0115] Step 1: prepare pure magnesium, pure zinc and magnesium-manganese master alloy as raw materials according to the composition ratio in Table 1;
[0116] Step 2: Melt in a protective atmosphere, first melt the magnesium ingot at 720-740℃, adjust the temperature to 740℃ after it is completely melted, add magnesium-manganese master alloy, and finally add pure zinc. After all the raw materials are melted, stir them fully, remove the surface scum, and quickly cool them with water to obtain a melt. The process conditions for solution treatment are: keep warm at 380℃ for 8h.
[0117] Step 3: hot extruding the ingot processed in step 2 to obtain a rod; the specific steps of hot extrusion are as follows:
[0118] The ingot was preheated at 350°C for 1 h and hot extruded at 350°C to obtain a rod with an extrusion ratio of 50:1 and an extrusion speed of 1.0 m / min.
[0119] Step 4: The rod obtained in step 3 is machined to a rod with a diameter of 5.0 mm to obtain a bio-magnesium-based composite material with a gradient structure. In step 4, the rotation speed of the rod is 100 r / min, the multi-directional rolling friction pressure of the rod is 200 N, and the radial deformation of the rod is 2.0%.
[0120] Comparative Example 6
[0121] Step 1: prepare pure magnesium, pure zinc and magnesium-manganese master alloy as raw materials according to the composition ratio in Table 1;
[0122] Step 2: Melt in a protective atmosphere, first melt the magnesium ingot at 720-740℃, adjust the temperature to 740℃ after it is completely melted, add magnesium-manganese master alloy, and finally add pure zinc. After all the raw materials are melted, stir them fully, remove the surface scum, and quickly cool them with water to obtain a melt. The process conditions for solution treatment are: keep warm at 380℃ for 8h.
[0123] Step 3: hot extruding the ingot processed in step 2 to obtain a rod; the specific steps of hot extrusion are as follows:
[0124] The ingot was preheated at 350°C for 1 h and hot extruded at 350°C to obtain a rod with an extrusion ratio of 50:1 and an extrusion speed of 1.0 m / min.
[0125] Step 4: The rod obtained in step 3 is machined to a rod with a diameter of 5.0 mm, and subjected to unidirectional rolling friction treatment to obtain a bio-magnesium-based composite material. In step 4, the rotation speed of the rod is 100 r / min, the unidirectional rolling friction pressure of the rod is 200 N, and the radial deformation of the rod is 2%.
[0126] The tensile mechanical properties of the magnesium-based composite materials prepared in Examples 5 to 6 were tested, and the results are shown in Table 6.
[0127] Table 6
[0128] Tensile strength(MPa) Yield strength (MPa) Elongation(%) Example 5 330 279 6.0 Example 6 319 261 9.5 Comparative Example 5 - -
[0129] The magnesium-based material rolls and rubs under unidirectional force, and the sample size accuracy is difficult to guarantee, and it may even cause problems such as bar bending. Figure 5 As shown in the figure. Three-way rolling friction causes the sample to be subjected to multi-directional pressure, which can ensure the stability of the rolling friction process and help eliminate defects. And under the same deformation, three-way rolling friction significantly improves the rolling friction efficiency and quality.
[0130] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the technical solution. Those skilled in the art should understand that those modifications or equivalent substitutions of the technical solution of the present invention that do not depart from the purpose and scope of the technical solution should be included in the scope of the claims of the present invention.
Claims
1. A bio-magnesium-based composite material with a gradient structure, characterized in that: Calculated by mass percentage, the magnesium-based composite material consists of the following components: 5.0% Mn, 3.5-6.5% Zn, inevitable impurity elements, the balance is Mg; The magnesium-based composite material has metal Mn particle reinforcements of dual scales of micrometer and nanometer, wherein the size of the Mn particle reinforcements in the magnesium-based composite material is 5-200nm and 1-20μm, and the grain size of the magnesium-based composite material is 50nm-30μm.
2. The magnesium-based composite material according to claim 1, characterized in that: When the magnesium-based composite material is a rod, the Mn particle size near its outer surface is 5nm-200nm; the size of the Mn particle reinforcement near the axis of the rod is nanometer and micrometer, the nanometer size is 5-200nm, and the micrometer size is 1-20μm.
3. The magnesium-based composite material according to claim 2, characterized in that: The grain size of the magnesium-based composite material gradually increases from its outer surface to its core.
4. The magnesium-based composite material according to claim 3, characterized in that: The grain size of the magnesium-based composite material gradually increases from 50 nm on the outer surface to 30 μm toward the core.
5. A method for preparing a bio-magnesium-based composite material, characterized in that: The magnesium-based composite material according to any one of claims 1 to 4 is prepared by the following specific steps: Step 1: prepare pure magnesium, pure zinc and magnesium-manganese master alloy as raw materials according to the component ratio; Step 2: Melting the raw materials prepared in step 1 to obtain a composite melt, rapidly cooling the composite melt to obtain an ingot, and performing a solid solution treatment on the ingot; Step 3: hot extruding the ingot processed in step 2 to obtain a rod; wherein the specific steps of hot extrusion are as follows: The ingot is preheated at 300-400°C for 1-2h, and hot extruded at 300-400°C to obtain a rod, with an extrusion ratio of (10:1)-(100:1) and an extrusion speed of 0.1-1.0 m / min; Step 4: Perform three-way rolling friction treatment on the rod obtained in step 3 to obtain a bio-magnesium-based composite material with a gradient structure; wherein the rod diameter is ≥1mm, the rotation speed of the rod is 10-100r / min, the rolling friction pressure of the rod is 10-200N, and the radial deformation is 2-6%.
6. The method according to claim 5, characterized in that: In step 2, smelting is carried out in a protective atmosphere environment. The magnesium ingot is first smelted at 720-740°C. After it is completely melted, the temperature is adjusted to 740°C, a magnesium-manganese intermediate alloy is added, and finally pure zinc is added. After all the raw materials are melted, they are fully stirred, the surface scum is knocked off, and they are quickly cooled to obtain a melt.
7. The method according to claim 5, characterized in that: In step 2, the process conditions of the solution treatment are: keeping warm at 380-420° C. for 6-12 hours.
8. The method according to claim 5, characterized in that: In the magnesium-based composite material after the treatment in step 3, micron- and nanometer-scale metal Mn particles are dispersed in the rods, and the sizes thereof are 1 to 20 μm and 5 to 200 nm; the size range of the grains in the magnesium-based composite material is 1 to 30 μm.
9. The method according to claim 4, characterized in that: In step 4, in the magnesium-based composite material after treatment in step 4, the size of the Mn particle reinforcement on its surface is 5 to 200 nm; the size of the Mn particle reinforcement inside it is 1 to 20 μm and 5 to 200 nm, and the grain size of the magnesium-based composite material gradually increases from the surface to the core, and is 50 nm to 30 μm.
